PENERAPAN MODEL PEMBELAJARAN CHILDREN LEARNING IN SCIENCE (CLIS) DALAM PEMBELAJARAN KONSEP DASAR IPA UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS DAN SIKAP ILMIAH MAHASISWA CALON GURU IPA SD - Wawan Eka Setiawan; Neri Egi Rusmana (Jurnal Pesona Dasar, 2018)
One of the problems encountered in science learning in school today that the learning process is less develop the skills and scientific attitude. Where science process skills and scientific attitudes are activities that must be developed at every level of education in science subjects. In this study, problems were developed about how the influence of CLIS learning models on the improvement of science process skills and scientific attitudes of PGSD students, other than that, the problem of how much improvement in science process skills and scientific attitudes of students when learning is carried out by applying the CLIS learning model. The research methodology used in this study is Pre-Experimental Designs, by using a research design One Group Pretest Posttest Design, wherein the implementation compares the pretest of science process skills and students' scientific attitudes with the posttest of science process skills and student scientific attitudes. Based on the data analysis that has been carried out the implementation of the CLIS learning model has a strong influence on student science process skills, also has a strong influence on the increasing scientific attitude of students, and improvement of science process skills using the CLIS model is included in the medium category, as well as the improvement of the scientific attitude of students included in the medium category. Based on the results of the analysis the researcher recommends to the dossiers, to the teacher, to the principal to make the CLIS learning model an alternative learning process in the classroom, as well as to the next researcher this research can be used as a reference in subsequent research.